Essentials of Coporate Finance / Stephen A Ross; Randolph Westerfield; Bradford D Jordan - Ross, Stephen A.
Essentials of Corporate Finance focuses on what undergraduate students with widely varying backgrounds need to carry away from a core course in business or corporate finance. The goal is to convey the most important concepts at a level that is approachable for the widest possible audience. Essentials is written in a relaxed, conversational style that invites the students to join in the learning process rather than being a passive information absorber.